Determinação sequencial de contaminantes inorgânicos em formulações minerais e fitoterápicas empregando métodos voltamétricos - Sant'Ana, Carla Simone (2011)
In this work, the voltammetric determination of the sequential elements Uranium, Vanadium, Antimony, Cadmium, Lead, Zinc, Chromium and Thallium have been studied in several arrays considering that all these elements are of some relevance from the toxicological point of view. The simultaneous and sequential determinations of metals by voltammetry has been widely studied in recent years due to the fact that they offer important advantages such as reducing analysis time and the decreased use of reagents. The metals U, V, Sb, Cd, Pb and Zn were determined by adsorptive cathodic stripping voltammetry (AdCSV) using chloranilic acid as a complexing agent at pH 2.3. Chromium was determined using DTPA as a complexing agent by adsorptive cathodic stripping voltammetry (AdCSV) at pH 6.2 and Tl was determined by anodic stripping voltammetry (ASV) using EDTA as a complexing agent at pH 4.6. Digestion methods by humid means were used in the samples. Methodology was used in the determining these elements as contaminants in fertilizers, medicinal plants and herbal formulations (both industrialized and manipulated). With the analysis of the proposed elements in different arrays, we obtained the following concentration ranges of these contaminants in the samples: Fertilizers - U 32.3 to 429.7 mg / kg, V 3.2 to 870mg/Kg; of Sb 60.1 to 215.1 mg / kg, Cd from 29.5 to 217.7 mg / kg, Pb from 69.9 to 529.5 mg / kg, Zn <15.4, Cr 14.1 to 422 , 1 mg / kg; Tl 0.4 to 20.8 mg / kg; Medicinal Plants - Pb from 32.8 to 143.0 mg / kg, Cd from 90.8 to 107.6 mg / kg; of Cr 11.6 to 20.5 mg / kg; Tl 5.6 to 33.7 mg / kg; Botanicals - V 98.0 to 1850.0 mg / kg; Sb 0.0 to 81.8 mg / kg, Pb from 155.8 to 336.5 mg / kg, Cd from 12.8 to 49.3 mg / kg, Cr 11.2 to 19.9 mg / kg and 19.4 to 332.9 mg, Tl mg/ Kg.